The Role of Co-Creation Value and Innovation Capability In Building Sustainable Competitive Advantage In Teaching Hospitals - Rian Puspitasari; Sartika Gani; Muthmainna Sri Dewi; Mifta Annajasi Muslimin; Laode Hidayat (Jurnal Kesehatan Manarang, 2026)
Increasing competition in Indonesia’s hospital industry requires teaching hospitals to adopt strategies beyond internal innovation by emphasizing collaborative value creation with stakeholders through Co-Creation Value (CCV).This study examines the direct effect of CCV on Sustainable Competitive Advantage (SCA) and its indirect effect through Innovation Capability (IC) at Universitas Hasanuddin Teaching Hospital. A quantitative explanatory design was applied using survey data from 263 employees selected through proportional stratified random sampling. Data were analyzed using covariance-based Structural Equation Modeling (SEM) with AMOS, and construct validity was assessed through Confirmatory Factor Analysis (CFA). CCV had a significant positive effect on IC (β = 0.869) and SCA (β = 0.880). However, IC did not have a significant effect on SCA (β = 0.020). The mediating effect of IC on the relationship between CCV and SCA was weak (indirect β = 0.018). CCV is a more dominant determinant of SCA than IC. In the context of a teaching hospital, sustainable competitive advantage is shaped more strongly by collaborative value creation involving patients and stakeholders than by innovation capability alone. Therefore, hospital management should prioritize co-creation strategies by strengthening stakeholder collaboration and patient engagement, while aligning innovation initiatives with organizational strategy, patient needs, and long-term institutional objectives.